Evaluasi Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan pada Masa Pandemi - Roni Parma; Fakhrina Hudayani; Arie Asnaldi (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
The problem in this research is the imbalance between student learning outcomes and the learning process during the pandemic. This study aims to determine the evaluation of sports and health physical education learning during the pandemic at the Pariaman City Elementary School. This research method uses a phenomological qualitative approach. The subjects in this study were students. Sources of data are obtained from secondary data, namely the results of observations of researchers in the field and primary data from interviews with related subjects. The interview technique was carried out in an unstructured manner using interview guidelines. The observation technique was carried out by two observers. The data analysis of this research is descriptive. The results of this study indicate: (1) Daring the online learning process students are not optimal in the learning process, this is because while online students study at home accompanied by parents, without meeting friends, and without being taught by the teacher directly. (2) Student learning outcomes are also high but the learning process is not optimal, so it becomes anxiety for parents because the knowledge gained is not optimal.